FLOATING MAXIM IN TV SHOW : RUMPI NO SECRET - Nena Nurjannah; Riris Resti Fujianti (PROJECT (Professional Journal of English Education), 2019)
TThe purpose of this study is to identify the techniques that lecturers use in assessing a conversation. Then to discover how the English lecturer makes conversation judgments using pragmatic techniques. several video conversations were selected as data in this study. The data obtained from the results observed a video on gossip tv shows and then in transcript and reported descriptive. The results of this study showed in a tv show there are several violations of maxim according to pragmatic techniques. From start violation of maxim quantity, quality, manner and relation. sources taken from a video on a tv show that talks about gossip and internet.Keywords: Floting, Maxim, Video on Gossip TV Show